ANALISIS KOMPETENSI CALON GURU MATEMATIKA DALAM PEMANFAATAN INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) PEMBELAJARAN MATEMATIKA - ZAI, EDISON; TELAUMBANUA, YAKIN NIAT; LASE, SADIANA; MENDROFA, NETTI KARIANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This research is motivated by the lack of ability of prospective mathematics teachers in utilizing Information and Communication Technology (ICT) in mathematics learning. Information and Communication Technology (ICT) is the most important thing in keeping up with current technological advances. The aim of carrying out this research is to determine the competence of prospective mathematics teachers in using Information and Communication Technology (ICT) in mathematics learning. This type of research is quantitative research with a descriptive approach. This was done to test how much prospective mathematics teachers have competence in utilizing Information and Communication Technology (ICT) in mathematics learning if they already become teachers. The research instruments used were questionnaires and structured interview questions consisting of several closed and open questions. The number of respondents who participated was 48 people from the Mathematics Education Study Program. Research results: the majority of prospective students in mathematics education study programs have basic knowledge of ICT and are familiar with the types of use of ICT in mathematics learning, as well as providing positive views/opinions towards the use of Information and Communication Technology in mathematics learning. ABSTRAKPenelitian ini dilatar belakangi oleh minimnya kemampuan calon guru matematika dalam pemanfaatan Information and Communication Technology (ICT) pada pembelajaran matematika. Information and Communication Technology (ICT) merupakan hal yang paling utama dalam mengikuti kemajuan teknologi pada saat ini. Tujuan pelaksanaan penelitian ini yaitu mengetahui kompetensi calon guru matematika dalam pemanfaatan Information And Communication Technology (ICT) dalam pembelajaran matematika. Jenis penelitian ini adalah penelitian kuantitatif dengan pendekatan deskriptif. Hal ini dilakukan untuk menguji seberapa besar calon guru matematika memiliki kompetensi dalam memanfaatkan Information and Communication Technology (ICT) dalam pembelajaran matematika jika sudah menjadi guru. Instrumen penelitian yang digunakan adalah angket (kuesioner) dan pertanyaan wawancara terstruktur yang terdiri dari beberapa pertanyaan bersifat tertutup dan terbuka. Jumlah responden yang berpartisipasi sebanyak 48 orang dari Program Studi Pendidikan Matematika. Hasil penelitian: sebagain besar mahasiswa/i calon guru program studi pendidikan matematika memiliki pengetahuan dasar terhadap ICT dan mengenal tentang jenis-jenis penggunaan ICT dalam pembelajaran matematika, serta memberikan pandangan/pendapat yang positif terhadap penggunaan Information and Communication Technology dalam pembelajaran matematika.